Managing performance in turbulent times : analytics and insight - Barrows, Ed, 1967-; Neely, A. D. (Andy D.) (Hoboken, N.J. : John Wiley & Sons, 2012)
'Straightforward playbook for executing world-class strategy for tangible resultsDesigned with three key ideas: leverage the tools that are working, simplify the model, and make the content readable for managers, Managing Performance in Turbulent Times is a road map for the modern strategy manager. Through their simplified execution process the authors--performance management experts--show executives how to get results and execute even in the most difficult conditions. Addresses importance of adaptability to change within today's business environment Explores the environmental turbulence that constantly confounds virtually all organizational systems, with workable solutions Provides a streamlined execution process any organization can use to improve business results Managers need tools to do their jobs better. Filled with proven solutions, this book reveals how to get results through successful strategy execution, presenting a process that will help your organization execute strategy in a simplified, efficient manner'--
Includes bibliographical references and index.
Keywords: Organizational effectiveness; Performance -- Management